The Influence of Fat Grafting on Breast Imaging after Postmastectomy Reconstruction: A Matched Cohort Analysis. Issue 6 (December 2020) - Cason, Roger W.; Shammas, Ronnie L.; Broadwater, Gloria; Glener, Adam D.; Sergesketter, Amanda R.; Vernon, Rebecca; Le, Elliot; Wickenheisser, Victoria A.; Marks, Caitlin E.; Orr, Jonah; Pyfer, Bryan J.; Hollenbeck, Scott T.
Abstract : Background: Fat grafting to the reconstructed breast may result in the development of benign lesions on physical examination, prompting further investigation with imaging and biopsy. The aim of this study was to assess the influence of fat grafting on the incidence of imaging and biopsies after postmastectomy reconstruction. Methods: Patients who underwent autologous or implant-based reconstruction following mastectomy from 2010 to 2018 were identified. Those receiving fat grafting as part of their reconstructive course were propensity matched 1:1 to those that did not with body mass index, reconstruction timing, and reconstruction type as covariates in a multivariable logistic regression model. Results: A total of 186 patients were identified, yielding 93 propensity-matched pairs. Fat-grafted patients had higher incidences of palpable masses (38.0 percent versus 18.3 percent; p = 0.003) and postreconstruction imaging (47.3 percent versus 29.0 percent; p = 0.01), but no significant difference in the number of biopsies performed (11.8 percent versus 7.5 percent; p = 0.32). Imaging was predominately interpreted as normal (Breast Imaging-Reporting and Data System 1, 27.9 percent) or benign (Breast Imaging-Reporting and Data System 2, 48.8 percent), with fat necrosis being the most common finding [ n = 20 (45.5 percent)]. No demographic, oncologic, reconstructive, or fat grafting–specific variables were predictive of receiving postreconstruction imaging on multivariate analysis. Fat grafting was not associated with decreased 5-year overall survival or locoregional recurrence-free survival. Conclusions: Fat grafting to the reconstructed breast is associated with increased incidences of palpable masses and subsequent postreconstruction imaging with benign radiographic findings. Although the procedure is oncologically safe, both patients and providers should be aware that concerning physical examination findings can be benign sequelae of fat grafting and may lead to increased imaging after breast reconstruction. Clinical Question/Level of Evidence: Therapeutic, III. Abstract : Supplemental Digital Content is available in the text.